Analysis of the Impact of Credibility, Attractiveness, and Influencer Content on Online Purchase Intention Through Live Streaming - Muhammad Zaldi Maulidin; Johny Natu Prihanto; Rajesh Prettypal Singh (Dinasti Publisher, 2025)
The rapid development of the social commerce industry and live streaming marketing influences consumer behavior in making purchase decisions. This study aims to examine the effects of influencer credibility and customer attitudes on brand awareness, brand association, and online purchase intention. The research employs a structural equation modeling (SEM) approach with a quantitative method, based on theories of influencer credibility and customer perception. Data were collected through questionnaires distributed to respondents who are potential buyers via live streaming, totaling 277 participants. This research makes a theoretical contribution by expanding the understanding of the influence mechanism of influencer credibility in the context of live streaming commerce, which is still limited in previous literature. Practically, the findings can assist brands in designing more effective influencer marketing strategies to improve sales performance through live streaming platforms.